Scientific Americans : invention, technology, and national identity - Branson, Susan (Cornell University Press, 2021)
"Scientific Americans examines the place of science and technology in American culture and the development of national identity from 1776 to 1876. Americans promoted inventions such as steam engines and civic projects such as water systems that articulated their national aspirations and pushed domestic industry to the forefront of progress"--